Inelastic Behavior of Eccentrically Braced Frames with Vertical Links: A Numerical Study - Shendri, Christina Natasha; Tjahjanto, Helmy Hermawan; Nugroho, Wivia Octarena; Pratiwi, Naomi (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
Eccentrically Braced Frames (EBFs) are seismic-resistant steel structures with horizontal or vertical energy-dissipating links designed to enhance ductility. To promote sustainability, future designs are moving toward easily replaceable structural systems that enable rapid post-earthquake rehabilitation. However, EBFs with horizontal links present challenges in repairing damaged links due to interference with other components, particularly beams. As an alternative, vertical links offer the potential to serve as